Influence of body composition on the bone mass of postmenopausal women - Marone, Marília Martins Silveira; Gouveia, Cecília Helena de Azevedo; Lewin, Shlomo; Wehba, Salim; Malvestiti, Luiz Fernando; Bianco, Antonio C. (São Paulo Medical Journal, 1997)
AIMS:To investigate the influence of body weight (BW), fat mass (FM) and lean mass (LM) on the bone mineral density (BMD) of several areas of the skeleton. PARTICIPANTS: Sixty one white postmenopausal women (50.1±4.8 years). MEASUREMENTS: Measurement of BMD by dual energy x-ray absorptiometry. The results were analyzed by linear regression and the slopes of each curve were compared. RESULTS: The results showed that the correlations between BW, FM and LM to BMD were positive, whilst the correlations between age and years since menopause to BMD were negative. LM was the main factor that influenced BMD in almost all areas. CONCLUSIONS: FM and LM present a positive effect on BMD, although LM is the main determinant of bone mass. Moreover, higher values of LM and FM present a protective effect against the reduction of BMD combined with menopause. Therefore postmenopausal women with low BW, especially low LM, present serious risk for developing osteoporosis.